Political Economy of Industrialization and Industrial Parks in Ethiopia - Selamawit G. Kebede; Almas Heshmati (Institute of Labor Economics (IZA), 2023)
This study investigates the political economy of industrialization in Ethiopia. It discusses the economic and political institutions during three political regimes and assesses the industrial sector's performance across these different regimes. Further, it evaluates the different industrial strategies and organizational structures for implementing the industrial policies together with the current industrial park strategy and its contemporary impact on employment creation, export promotion, foreign exchange revenues, the value chain, and spillover effects. Both qualitative and quantitative approaches are used for exploring the role of political economy in Ethiopian industrialization. Different political strategies were followed by the political regimes to support the industrial sector. The paper distinguishes between two extreme political strategies of protectionist import substitution industrialization and the outward strategy of export-oriented industrialization. The study confirms that political institutions negatively impacted industry for several decades. The results support focusing on institutions to successfully implement industry policies for inducing the industrialization process in the country. Policies must be implemented considering existing opportunities and resources in the country along with their respective economic outcomes instead of excessive priority being given to the political interests of the regime in power.
Keywords: J24; O14; O25; O47; P48; 330; industrialization; industrial parks; political economy; industrial strategy; industry growth; Ethiopia